The Effect of NPK Fertilizer Dosage and Growth Regrowth (ZPT) Against Sweet Corn Growth And Production (Zea mays Saccharata L.) - A Miftakhurrohmat; Pipit Putrianingsih (Nabatia, 2017)
Sweet corn is an agricultural commodity that has potential value and is very popular with the community. This study aims to determine the effect of NPK fertilizer and plant growth regulator (ZPT) dosage on the growth and production of sweet corn, the study was conducted in June-August 2017 in Jiken Village, Tulan- gan Sub-district, Sidoarjo Regency and Agricultural Laboratory of Agrochemical Faculty of Agriculture Muhammadyah Sidoarjo University. The experiment was arranged facto- rially by using Group Randomized Block Design (RAK) which was repeated three times. The first factor is the dose of NPK fertilizer, which includes 250 kg/ha, 300 kg/ha, and 350 kg/ha. The second factor is the dose of Atonic ZPT, which includes 0 L/ha (con- trol), 1 L/ha, dan 2 L/ha. The variables observed were plant height, number of leaves, stem diameter, weight of cob weighted per plant, weight of sterile per plant, length of cob, and diameter of cob. The result of the research showed that there was interaction effect between the treatment of NPK fertilizer dosage and the dosage of ZPT Atonik on high observation variable and the number of leaves age 39 HST, and the weight of wet stover. The dosage of NPK fertilizer showed significant effect on plant height, leaf num- ber, stem diameter, weight of cob weighted per plant, cob diameter, ear length, and wet stalk weight. The dose of ZPT showed a significant effect on vegetative growth that is of leaf number, stem diameter, cob diameter, and weight of wet stover.